Can’t See the Wood For the Logframe: Integrating Logframes and Theorie s of Change in Development Evaluation - Freer, Gordon; Lemire, Sebastian (Canadian Journal of Program Evaluation, 2019)
There are numerous ways in which to model the underlying theory of pro grams. In the context of international development evaluation, the mos t ubiquitous are likely “logframes” and to some extent “theories of ch ange,” both of which may serve to guide program development and manage ment, monitoring, and evaluation. While logframes and theories of chan ge are often developed in parallel, they are rarely fully integrated i n their practical application. Drawing on lessons from a recent theory -based evaluation, this article argues that fully integrating the prog ram theory of change within the program logframe provides for a strong er and more holistic understanding of program progress.